2018
DOI: 10.1088/1361-6463/aac249
|View full text |Cite
|
Sign up to set email alerts
|

FMR-driven spin pumping in Y3Fe5O12-based structures

Abstract: Ferromagnetic resonance driven spin pumping, a topic of steadily increasing interest since its emergence over two decades ago, remains one of the most exciting research fields in condensed matter physics. Among the many materials that have been explored for spin pumping, yttrium iron garnet (YIG) is one of the most extensively studied because of its exceptionally low magnetic damping and insulating nature. There is a great amount of literature in the spin pumping and related research fields, too broad for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 286 publications
0
37
0
6
Order By: Relevance
“…Epitaxial α-Fe2O3 films are grown on Al2O3(001) at 500°C, followed by in-situ deposition of a Pt layer on α-Fe2O3 at room temperature using off-axis sputtering. [27][28][29] α-Fe2O3 is a high temperature AFI with a corundum structure as shown in Fig. 1a.…”
mentioning
confidence: 99%
“…Epitaxial α-Fe2O3 films are grown on Al2O3(001) at 500°C, followed by in-situ deposition of a Pt layer on α-Fe2O3 at room temperature using off-axis sputtering. [27][28][29] α-Fe2O3 is a high temperature AFI with a corundum structure as shown in Fig. 1a.…”
mentioning
confidence: 99%
“…However, not only non-magnetic normal metals can be used as ISHE spin current detectors. In a number of works, it was shown that magnetic metals, such as permalloy Py (NiFe), as well as Fe, Co, Ni can be used as spin current detectors [3][4][5]. TbCo 2 /FeCo structures containing Tb element with a strong spin-orbit interaction (high atomic weight Z) are distinguished by giant magnetostriction, a large value of the magnetomechanical coupling coefficient, controlled induced magnetic anisotropy and the ability to induce spin-orientation transitions by a magnetic field or elastic stresses [6,7].…”
Section: Spin Interactions At the Interfaces Ferromagnetic Oxide/ferrmentioning
confidence: 99%
“…Films from Y 3 Fe 5 O 12 (YIG) are very attractive for spintronic structures because of the small magnetic attenuation and the fact that they are an insulator. It was reported that the spin current can be excited in YIG and detected with a Py film [3][4][5].…”
Section: Spin Current In Tcfc/y 3 Fe 5 O 12 Structurementioning
confidence: 99%
“…YIG(35 nm)/NiO(t NiO )/Pt(5 nm) trilayers were deposited using off-axis sputtering on Gd 3 Ga 5 O 12 (GGG) (111) substrates [19]. (111)-textured NiO layers with thicknesses from 0.5 to 40 nm were grown at RT [10].…”
mentioning
confidence: 99%
“…The very large V ISHE = 2.38 mV provides a dynamic range of four orders of magnitude for this study. Since for YIG 4πM s < H res and M essentially follows (but lags behind) H, a (quasi-)sinusoidal dependence of V ISHE on θ H is expected, which is regarded as a signature of spin pumping [19].…”
mentioning
confidence: 99%